Prony’s method applied to anomalies’ separation on an Andean cordillera section - Introcaso, Beatriz (1998)
Prony's method is applied in this paper to separate gravity anomalies on an E-W section near 22° S in Western South America. The method allows us to fit the coefficients in a linear combination of exponentials representing the gravity field power spectrum, to obtain an estimate of the causative masses and depths. For the profile under consideration the results agree with geological models of the area. Some possible difficulties of the method are mention.